PUMPING STATIONS TO ENSURE GUARANTEED WATER SUPPLY FROM WATER SUPPLY CHANNELS (Modern American Journal of Engineering, Technology, and Innovation, 2025)
The article discusses the need to maintain an optimal water level in the pre-chambers and prevent their oscillations to ensure normal, stable operation of the pumping units. The article presents methods for improving the operation of the units, not only by increasing the maximum possible rise in the water level in the water intake chamber. Based on the developed methods, it is possible to stabilize the supply of pumping stations and increase their efficiency. The article also develops new operating modes of canal robots with maintaining a high water level in the advance chambers, based on recommendations for improving the operating mode of NS-1, development of scientific research and direct practical experience in operation.